The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4314/jafs.v18i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the viability of climate adaptation strategies of cassava-based farmers in southern Nigeria

Abstract: The study examined the viability of climate adaptation strategies of cassava-based farmers in Southern Nigeria. A total of 300 cassava-based farmers were randomly selected. Primary data were obtained through administration of questionnaire, interview schedule and Focus Group Discussion (FGD). Data were analysed using descriptive statistics which involved the use of percentages, mean and frequency distributions as well as OLS multiple regression model. The specific objectives include: to describe the socio-econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…All these problems are as a result of human activities by application of conventional farming knowledge and technology to the environment. This is in line with Henri-ukoha (2020) who claimed that climatic change is as a result of human activities and it affects agriculture more than any other sector [19]. Whatever that affects agriculture in Nigeria affects the greater percentage of the country entire populace.…”
Section: Environmental Degradationsupporting
confidence: 82%
See 2 more Smart Citations
“…All these problems are as a result of human activities by application of conventional farming knowledge and technology to the environment. This is in line with Henri-ukoha (2020) who claimed that climatic change is as a result of human activities and it affects agriculture more than any other sector [19]. Whatever that affects agriculture in Nigeria affects the greater percentage of the country entire populace.…”
Section: Environmental Degradationsupporting
confidence: 82%
“…Amongst the impact of this conventional technologies on the environment included the misuse and damage of our natural earth and the main two ways this damage have occurred, are through air and water pollution and depletion of natural resources. Henri-Ukoha (2020) noted that Global warming which causes environmental unsustainability is as a result of climatic change which emanated from the activities of man such as fossil fuel burning, deforestation, industrialization which affects the livelihood of the people and eco-system deeply [19]. All these is as a result of the use of conventional technologies and synthetic products in our environment especially agriculture that is practiced by about 80.0 percent of the entire populace of Nigeria.…”
Section: The Role Of Green Technologies For Environmental Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…AMONG RURAL WOMEN FARMERS IN NIGERIA The challenges faced by rural women farmers in adapting to climate change is widely documented in literature. Henri-Ukoha [33], [34] reported that farmers cannot afford to procure the necessary inputs and resources required to practice adaptation in Southern Nigeria. In their work on challenges faced by cocoyam farmers in adapting to climate change in Southeast Nigeria, Ifeanyi-Obi et al [7] reported that lack of and high cost of farm inputs and low soil fertility, land and labour, poor access to information and ineffectiveness of cooperatives, lack of/poor access to fund and credit facilities and poor government support, lack of improved varieties of cocoyam, poor value attached to cocoyam, poor infrastructural capacity and technology knowhow and transportation were the challenges faced by farmers in adapting to climate change impacts in Nigeria.…”
Section: Challenges To Climate Change Adaptationmentioning
confidence: 99%
“…Despite the various perspectives covered by the existing literature on ICT use in extension delivery (Ifeanyi-obi et al, 2023;Henri-Ukoha, 2020;Nwaiwu et al, 2019;Rengaraj and Shibu, 2022;Onyeneke et al, 2019;Chimanga and Kanja, 2020;Ekeanya et al, 2018), the drivers (dimensions) of accessibility and use of ICTs by Ghanaian cocoa farmers are less studied.…”
Section: Introductionmentioning
confidence: 99%